POTENSI PENERIMAAN RETRIBUSI IMB PERUMAHAN KPR BTN SEBAGAI SALAH SUMBER PAD KOTA KENDARI - Tadjuddin Tadjuddin; Muhammad Natsir (Universitas Halu Oleo, 2017)
Although the PAD of Kendari City from year to year has increased, but when compared with the APBD, it appears that the portion of PAD to regional expenditure is still very small, which is an average of 7.79% in the period 2002-2008. This study aims to determine (1) the potential revenue of IMB from KPR BTN in Kendari City, (2) Willingness of the community owners of BTN KPR who have renovated their houses to manage IMB, and (3) know the aspirations or proposals of the community in order to realize their IMB . The results of the research show that the receipt of IMB retribution on total regional revenues is quite large, the potential for IMB revenue from retribution is still quite large. the service performance was quite good, but the community still wanted an improvement plan. All respondents did not have a new IMB, the people who had renovated their houses were willing to take care of the new permit. In the context of smooth management of IMB, the government needs to pay attention to the aspects of costs, bureaucracy, services, procedures, extortion, socialization, transparency and time for managing IMB.